THE EFFECT OF SATISFACTION AND TRUST ON MEMBER LOYALTY RELOAD byHP - Paramitha Utami; Innocentius Bernarto; Zoel Hutabarat (SEAN Institute, 2023)
This study aims to examine the effect of satisfaction and trust on member loyalty at the Reload byHP fitness center, Jakarta. This research is quantitative research by distributing questionnaires and managed to collect as many as 230 respondents. Respondent data that was collected was then processed using SmartPLS 3.0 software. The test results in this study indicate that satisfaction and trust have a positive and significant effect on Reload byHP member loyalty, both direct and indirect effects. The satisfaction felt by members builds members' trust in other programs and services provided by Reload byHP. Reload byHP can also be more confident about the standard of services and programs provided by Reload byHP for its members. Satisfaction and trust that is formed in members should be maintained by maintaining existing service standards.